2018
DOI: 10.1155/2018/1469651
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals of Central Aortic Blood Pressure and Augmentation Index Assessed with an Oscillometric Device in Healthy Children, Adolescents, and Young Adults from Argentina

Abstract: Age-related reference intervals (RIs) of central (aortic) systolic blood pressure (cSBP) and augmentation index (cAIx) obtained from large healthy population are lacking in Argentina (South America). Aims. To analyze the existence of associations among cSBP and cAIx with demographic, anthropometric, and hemodynamic parameters and to generate percentile curves and RIs adjusted to each level of age and gender and/or body height. cSBP and cAIx were measured in 1038 healthy children, adolescents, and young adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
9
0
3
Order By: Relevance
“…Children with obesity have been reported to present with lower AIx compared with normal weight children ( 12 ). A negative correlation has been reported between body mass index (BMI) and central AIx ( 14 ). However, some studies found no association of childhood obesity with AIx ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children with obesity have been reported to present with lower AIx compared with normal weight children ( 12 ). A negative correlation has been reported between body mass index (BMI) and central AIx ( 14 ). However, some studies found no association of childhood obesity with AIx ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Существуют два подхода к оценке ригидности магистральных артерий: одномоментная оценка и определение в ходе суточного мониторирования АД. Одномоментная оценка более целесообразна для проведения крупных популяционных исследований [21][22][23]. Значения артериальной жесткости могут варьировать в течение суток и зависят от положения пациента, степени физической активности и других факторов.…”
Section: Discussionunclassified
“…до 113 мм рт.ст., у мальчиков -от 97,7 до 116,9 мм рт.ст. Эти показатели были ниже, чем в немецкой популяции [22]. Оценка центрального АД у студентов по данным одномоментного определения параметров центральной и периферической гемодинамики при использовании осциллометрического метода позволила установить, что факторы риска развития сердечно-сосудистых заболеваний ассоциируются с нарушением жесткости магистральных артерий в виде повышения центрального систолического АД и скорости распространения пульсовой волны [7].…”
Section: таблица 5 взаимосвязь уровней артериальной ригидности и средних значений суточного мониторирования периферического артериальногоunclassified
See 1 more Smart Citation
“…A number of epidemiological studies have used adult-validated devices to establish cSBP and cAIx references values in children [29][30][31][32]. Furthermore, ongoing hemodynamic research in the young has led to promising developments for a potential role of central hemodynamic indices as tools for cardiovascular risk stratification or markers of early disease [33][34][35].…”
Section: Discussionmentioning
confidence: 99%